Relationship Between Maternal And Fetal Resistin Levels in Obesity nnd Normal to Anthropometry Newborn Babies - Siska Anggraini; Yusrawati Yusrawati; Mayetti Mayetti (Universitas Andalas, 2018)
Status of excess nutrition (obesity) and less influence on fetal growth. Obesity has increased fat, which increases some adipokines, one of which is resistant. Resistin plays a role in maintaining glucose homeostasis by inducing insulin resistance, antiadipogensis and inflammation. Resistin is found in the baby's umbilical cord so that resistin can play a role in fetal growth. The purpose of this study was to evaluate differences in maternal resistin levels between obese and normal weight mothers and their relationship to anthropometry of newborns. Material and Matode: This research is an observational analytic study with cross-sectional design. Subjects consisted of 20 obese mothers and 20 normal weight people. Sampling was done by consecutive sampling at Dr. M. Djamil Padang, dr. Rasidin Padang and TK III Reksodiwiryo Padang Hospital, Indonesia. Blood samples were measured by spectrophotometry. Statistics were analyzed by Mann Whitney U-Test and Spearman Test. Results: Median maternal resistin in obese subjects and normal weight was 1406 (1024.31-1947.78) ng / L and 1308.46 (740.16-1521.56) ng / L (p <0.05). Median fetal resistin in obese subjects and normal weight was 1086.47 (820.09-2205.29) ng / L and 1077.59 (704.65-1654.76) ng / L (p> 0.05). Conclusion: There was a relationship between maternal resistin and newborn body weight with r = -0.412 (p <0.05). There was a correlation between fetal resistin levels with the weight of newborns and infant body length (r = -0.694, and r = -0.455) (p <0.05). Resistin levels affect fetal weight gain in the obese and normal weight.